Individual exposure to traffic related air pollution across land-use clusters. (July 2016) - Shekarrizfard, Maryam; Faghih-Imani, Ahmadreza; Crouse, Dan L.; Goldberg, Mark; Ross, Nancy; Eluru, Naveen; Hatzopoulou, Marianne
Highlights: We investigated the relationship between personal emissions of NO x and exposure to NO2 . The highest emitters have the lowest exposure and reside in the peripheral areas. We investigated the effect of accounting for daily mobility when estimating exposure. NO2 exposures derived from tracking daily mobility are higher than NO2 concentrations at home. Abstract: In this study, we estimated the transportation-related emissions of nitrogen oxides (NO x ) at an individual level for a sample of the Montreal population. Using linear regression, we quantified the associations between NO x emissions and selected individual attributes. We then investigated the relationship between individual emissions of NO x and exposure to nitrogen dioxide (NO2 ) concentrations derived from a land-use regression model. Factor analysis and clustering of land-uses were used to test the relationships between emissions and exposures in different Montreal areas. We observed that the emissions generated per individual are positively associated with vehicle ownership, gender, and employment status. We also noted that individuals who live in the suburbs or in peripheral areas generate higher emissions of NO x but are exposed to lower NO2 concentrations at home and throughout their daily activities. Finally, we observed that for most individuals, NO2 exposures based on daily activity locations were often slightly more elevated than NO2 concentrations at the home location. We estimated that between 20% and 45% of individuals experience a daily exposure that is largely different from the concentration at their home location. Our findings are relevant to the evaluation of equity in the generation of transport emissions and exposure to traffic-related air pollution. We also shed light on the effect of accounting for daily activities when estimating air pollution exposure.